High-capacity layered-spinel two-phase composite doped lithium manganate and preparation method thereof
By doping metal elements in lithium manganate and controlling the molar ratio, a two-phase composite doped lithium manganate with both C2/m layered and Fd-3m spinel structure was prepared, which solved the shortcomings of existing materials in terms of capacity, magnification and cyclic stability, and achieved high capacity, low cost and excellent performance.
Patent Information
- Application Number
- CN202211358484.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-01
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-11-01
AI Technical Summary
The existing lithium manganate-based battery positive electrode materials have shortcomings in capacity, rate performance and cycle stability, and are costly, making it difficult to meet the needs of high capacity and low cost.
By doping a small amount of metal elements, such as Al, Cr, Co, etc., and controlling the molar ratio of lithium, manganese and doped elements, a two-phase composite doped lithium manganese oxide with a C2/m layered structure and an Fd-3m spinel structure was prepared.
It achieves high discharge capacity, excellent rate performance and better cycle stability of the material. It also has more irreversible capacity for the first cycle. It is suitable for different application scenarios and has an additional lithium supplement effect in the whole battery system.
Smart Images

Figure CN115621449B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery positive electrode materials, and in particular to a high-capacity layered-spinel two-phase composite doped lithium manganate and a preparation method thereof. Background Art
[0002] Ternary layered materials are cathode materials that currently occupy a large market share. Although the current high nickel content can improve the specific capacity of ternary layered cathode materials, it will also increase the difficulty of material preparation and storage and reduce the material's cycle stability and thermal stability. In addition, the recent continuous rise in the price of Ni elements has also greatly increased the cost of high-nickel layered cathode materials. Therefore, low-cost Mn-based cathode materials have received more and more attention.
[0003] Spinel lithium manganese oxide LiMn2O4 is a cathode material that has long been commercialized. Although the three-dimensional Li diffusion channel in the material structure gives it excellent rate performance, it is limited by its low theoretical specific capacity (~145mAh / g), and its actual specific capacity has gradually failed to meet current needs. Layered LiMnO2 is another Mn-based cathode material with potential application value. This material has a high theoretical specific capacity (~285mAh / g) at a low charging voltage, and has the characteristics of easy preparation and storage, low cost, and environmental friendliness.
[0004] LiMnO2 usually has two structural types, namely orthorhombic LiMnO2 belonging to the Pmnm space group and monoclinic LiMnO2 belonging to the C2 / m space group, but both structures of lithium manganese oxide have some shortcomings. Among them, the Pmnm structure LiMnO2 with a zigzag arrangement of transition metals is a thermodynamically stable phase, so it can be prepared by the traditional high-temperature solid phase method, but because this structure is not conducive to Li + The diffusion of LiMnO2 is very low (50-100 mAh / g) and has no practical application value. LiMnO2 with C2 / m structure has a traditional layered structure, which is conducive to the + The actual discharge capacity is relatively high (150-200 mAh / g) due to the deintercalation of the LiMnO2 structure. However, the LiMnO2 structure is a metastable phase and can only be prepared by liquid phase methods (such as hydrothermal method and ion exchange method), which is not conducive to large-scale production. Studies have shown that by adding a small amount of Al 3+ ,Cr 3+ Replace Mn 3+ C2 / m layered structure lithium manganese oxide can be prepared by a high-temperature solid phase method, but the poor rate performance and large irreversible capacity loss in the first cycle of this material affect its application.
[0005] Patent CN102751482A discloses a non-doped lithium manganese oxide positive electrode material prepared by high-temperature solid phase sintering and having both spinel and layered structures, and its composition is LixMn2O4, where x=1.1-1.9. Although the mixed crystal structure lithium manganese oxide positive electrode material has some advantages of both structures, it also has obvious shortcomings: (1) It can only obtain orthorhombic LiMnO2 with Pmnm structure by high-temperature solid phase method, so LiMnO2 in mixed crystal structure lithium manganese oxide is actually a structure with very poor performance, and its presence in the material will be detrimental to the performance of capacity and rate performance; (2) The capacity attenuation problem of Mn-based materials during long cycles (caused by the distortion of trivalent Mn and Mn dissolution) has not been improved in this material. Patent CN109088067A discloses a method for preparing a low-cobalt doped spinel-layered structured nickel manganese lithium two-phase composite positive electrode material, but the material is a nickel manganese positive electrode material. According to its raw material ratio, it can be seen that: (1) the layered phase belongs to the R-3m space group. The layered material of this structure has a limited charging capacity and a high initial efficiency, so there is no additional lithium supplementation effect; (2) the spinel phase is a 4.8V high-voltage spinel, and the current commercial electrolyte cannot withstand its excessively high working voltage. In addition, the material uses a large amount of Ni element, so the cost is relatively high.
[0006] Therefore, how to prepare a low-cost lithium manganese oxide-based battery positive electrode material with high capacity, high rate and high cycle stability is an urgent problem to be solved. Summary of the invention
[0007] The purpose of the present invention is to provide a high-capacity, low-cost layered-spinel two-phase composite doped lithium manganese oxide and a preparation method thereof. By doping a small amount of metal elements into the lithium manganese oxide and controlling the molar ratio of lithium, manganese and the doping elements, a two-phase composite doped lithium manganese oxide with both a C2 / m layered structure and a Fd-3m spinel structure is obtained. The material not only has excellent discharge capacity, rate performance and cycle stability, but also can play an additional lithium supplement effect in the full battery system, which further expands the application of low-cost lithium manganese oxide-based positive electrode materials in full batteries.
[0008] To achieve the above object, the present invention provides a high-capacity layered-spinel two-phase composite doped lithium manganate, the structural formula of which is Li x Mn 1-y M yO2, wherein x=0.51-0.99, y=0.01-0.25, M is one or more of Al, Cr, Co, Fe, Mg, Ti, V, Ni, Cu, Zn, Zr, Nb, Mo, W, Ca, Y, La, Ce, Ga, In; and includes C2 / m layered structure and Fd-3m spinel structure. M is preferably one or more of Al, Cr, Co, Zr, Nb, Mo, W, Ca, Y, La, Ce, Ga, In. By controlling Li / (Mn+M) to 0.51-0.99 and controlling the content of doping element M to 0.01-0.25, the material has both C2 / m layered structure and Fd-3m spinel structure. The doped lithium manganate of this structure has excellent discharge capacity, rate performance and cycle stability, and can also play an additional lithium supplement effect in the full battery system.
[0009] Furthermore, the x is preferably 0.65-0.99, preferably 0.85-0.99.
[0010] Furthermore, the molar ratio of the C2 / m layered structure to the Fd-3m spinel structure is (1%:99%)-(99%-1%), preferably (10%:90%)-(99%-1%), and more preferably (50%:50%)-(99%-1%). By controlling the relative content of the C2 / m layered structure and the Fd-3m spinel structure, the discharge capacity, rate performance, cycle stability and first efficiency of the material can be regulated, so that it is suitable for different application scenarios.
[0011] Further, when the cut-off voltage is 2.5-4.3V, the 0.1C first charge capacity of the high-capacity layered-spinel two-phase composite doped lithium manganese oxide is 150-270mAh / g, preferably 220-270mAh / g, and the first efficiency is 50%-90%, preferably 50%-80%, that is, preferably Li with x between 0.65-0.99 x Mn 1-y M y O2 material. The first efficiency of the two-phase composite doped lithium manganese oxide of the present invention is improved compared with the layered single-phase lithium manganese oxide, but it still has a large irreversible capacity of the first cycle. Therefore, it can be combined with the high first efficiency lithium ion battery positive electrode material as a positive electrode material, and the irreversible release of Li in the first cycle is used to offset the active Li consumed by the formation of the SEI film at the negative electrode, thereby improving the initial capacity and cycle performance of the battery.
[0012] The present invention also provides a method for preparing the high-capacity layered-spinel two-phase composite doped lithium manganate as described in any one of the above, comprising:
[0013] The Li compound, the Mn compound and the metal M compound are weighed in a stoichiometric ratio, mixed evenly by a solid phase method or a liquid phase method, and the mixed dry materials are calcined at a high temperature to obtain the high-capacity layered-spinel two-phase composite doped lithium manganate.
[0014] Furthermore, the Li compound includes one or more of lithium carbonate, lithium oxide, lithium hydroxide and lithium nitrate; the Mn compound is one or more of manganese oxide, hydroxide, carbonate, nitrate, chloride and sulfate; the metal M compound is one or more of the oxide, hydroxide, carbonate, nitrate, chloride and sulfate corresponding to the metal M.
[0015] Furthermore, the high temperature calcination temperature is 500-1000° C., and the calcination time is 2-25 hours.
[0016] Preferably, the high-temperature calcination is carried out in a mixed atmosphere of an inert gas and oxygen, and the molar ratio of the inert gas to oxygen is 1:(0.01-100), preferably 1:(0.1-10). The preparation of the target product can be achieved under the calcination temperature and atmosphere defined in the present invention. The key influencing factor of the present invention lies in the ratio of each element. By adjusting the ratio of raw materials, according to the commonly used method for preparing lithium manganate positive electrode materials, composite phase doped lithium manganate can be prepared.
[0017] Furthermore, the solid phase method includes ball milling or sufficient mixing by a high-speed mixer, the ball milling speed is 200-800r / min, the ball milling time is 1-72h, and the ball-to-material weight ratio is (5-50):1; the speed of the high-speed mixer is 500-10000r / min, and the mixing time is 1-72h.
[0018] Furthermore, the liquid phase method dissolves the soluble salts corresponding to Mn and M in water to obtain a liquid phase mixture; then, an excess of soluble alkali or soluble carbonate is added dropwise to the liquid phase mixture under stirring to form a precipitate of Mn and M; the precipitate is filtered, washed, and dried to obtain a dry material; and the dry material is evenly mixed with a Li compound by a solid phase method.
[0019] The beneficial effects of the present invention are as follows:
[0020] 1. The high-capacity layered-spinel two-phase composite doped lithium manganate provided by the present invention is obtained by doping a small amount of metal elements in the lithium manganate and controlling the molar ratio of lithium, manganese and doping elements to obtain a two-phase composite doped lithium manganate with both C2 / m layered structure and Fd-3m spinel structure. The material not only has excellent discharge capacity, rate performance and cycle stability, but also has more first cycle irreversible capacity compared with other commercial positive electrode materials. By controlling the relative content of the C2 / m layered structure and the Fd-3m spinel structure, the discharge capacity, rate performance, cycle stability and first effect of the material can be regulated, so that it is suitable for different application scenarios.
[0021] 2. The introduction of metal ions M inhibits the formation of Pmnm orthorhombic lithium manganese oxide with poor performance and induces the formation of C2 / m layered lithium manganese oxide with better performance. 3+ Can alleviate the spinel structure due to Mn 3+ The lattice distortion caused by the Jiang-Taylor distortion and the Mn 3+ The Mn dissolution problem caused by the disproportionation reaction is eliminated, so the doped composite material has better initial capacity, rate and cycle performance.
[0022] 3. Advantages of the two-phase composite structure of the present invention: (1) The irreversible capacity of the first cycle of the Fd-3m spinel phase in the composite structure is low, and its three-dimensional Li diffusion channel is conducive to the internal Li deintercalation in the composite structure material, thus being superior to the single-phase layered LiMn C2 / m structure. 1-y M y O2 materials have higher first efficiency and better rate performance than layered-spinel composite materials; (2) The C2 / m layered phase in the composite structure has more Li that can be deintercalated, so it is different from the single-phase spinel Li in the Fd-3m structure. 0.5 Mn 1-y M y O2 materials have higher capacity than layered-spinel composite materials. (3) The layered-spinel composite structure is beneficial to inhibit the lattice distortion of lithium manganese oxide materials along the same direction during the process of Li insertion and deinsertion, so the layered-spinel composite structure of lithium manganese oxide materials has better cycle stability.
[0023] 4. The high charging capacity and low first efficiency of the C2 / m layered phase in the composite structure can play an additional role in replenishing lithium in the whole battery system (especially when a negative electrode with a lower first efficiency is selected for matching), thereby offsetting the irreversible consumption of Li in the formation of the SEI film, which is beneficial to the improvement of the initial capacity and cycle performance of the lithium manganese oxide material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 It is a schematic structural diagram of the high-capacity layered-spinel two-phase composite doped lithium manganate provided by the present invention;
[0026] Figure 2 This is the XRD spectrum of the high-capacity layered-spinel two-phase composite doped lithium manganese oxide prepared in Example 1. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] A high-capacity layered-spinel two-phase composite doped lithium manganese oxide, with the chemical formula Li 0.9 Mn 0.9 Cr 0.1 O2, lithium carbonate, manganese dioxide and chromium oxide are used as raw materials, mixed by a solid phase mixing method, and then calcined at 900°C for 10 hours to obtain layered-spinel two-phase composite doped lithium manganate.
[0030] XRD of Example 1 ( Figure 2 ) The results show that the main diffraction peak of the product can be attributed to the C2 / m layered structure. In addition, the diffraction peak corresponding to the Fd-3m spinel structure also appears, which indicates that: (1) the material prepared in Example 1 has a layered-spinel composite structure; (2) the introduction of a small amount of Cr can induce the formation of a C2 / m layered phase with better performance, while inhibiting the appearance of Pmnm orthorhombic lithium manganese oxide with poor performance in the composite structure material.
[0031] Comparative Example 1
[0032] A layered single-phase doped lithium manganese oxide with the chemical formula LiMn 0.9 Cr 0.1 O2. Lithium carbonate, manganese dioxide and chromium oxide are used as raw materials, mixed by a solid phase mixing method, and then calcined at 900°C for 10 hours to obtain layered single-phase doped lithium manganate.
[0033] Comparative Example 2
[0034] A layered-spinel two-phase composite lithium manganese oxide, with the chemical formula Li 0.9 MnO2. Lithium carbonate and manganese dioxide are used as raw materials, mixed by a solid phase mixing method, and then calcined at 900°C for 10 hours to obtain a two-phase composite lithium manganate.
[0035] Table 1 Performance test results of Example 1 and Comparative Examples 1-2
[0036]
[0037] It can be seen from Table 1 that (1) since the main phase in the doped lithium manganese oxide composite structure material of Example 1 is the C2 / m layered phase, the capacity and rate performance (3C discharge capacity) of the material are much higher than those of the non-doped lithium manganese oxide composite structure material mainly composed of the Pmnm phase in Comparative Example 2; and the substitution of the metal ion M for Mn suppresses the Jan-Taylor effect of trivalent Mn and the Mn dissolution problem, so Example 1 has a better cycle performance than Comparative Example 2.
[0038] (2) The presence of a small amount of spinel phase in the doped lithium manganese oxide composite structure material of Example 1 makes the initial capacity and rate performance (3C discharge capacity) of the material significantly higher than that of the C2 / m single-phase layered material in Comparative Example 1, and the formation of the composite phase inhibits the lattice distortion of the lithium manganese oxide material in the same direction during the process of Li insertion and deinsertion, so the cycle performance of Example 1 is also improved compared with Comparative Example 1. It can be seen that the introduction of a small amount of spinel structure is helpful to improve the initial capacity, rate and cycle performance of the material, and the first efficiency of the material does not change much, so it can also be used for lithium replenishment of the full battery system.
[0039] Example 2
[0040] A high-capacity layered-spinel two-phase composite doped lithium manganese oxide, with the chemical formula Li 0.9 Mn 0.75 Cr 0.25 O2, lithium carbonate, manganese dioxide and chromium oxide are used as raw materials, mixed by a solid phase mixing method, and then calcined at 700°C for 10 hours to obtain layered-spinel two-phase composite doped lithium manganate.
[0041] Example 3
[0042] A high-capacity layered-spinel two-phase composite doped lithium manganate with a structural formula of Li 0.9 Mn 0.95 Cr 0.05 O2. Lithium carbonate, manganese dioxide and chromium oxide are used as raw materials, mixed by a solid phase mixing method, and then calcined at 650°C for 15 hours to obtain layered-spinel two-phase composite doped lithium manganate.
[0043] Example 4
[0044] A high-capacity layered-spinel two-phase composite doped lithium manganate with a structural formula of Li 0.95 Mn 0.85 Cr 0.1 Fe 0.05 O2. Lithium carbonate, manganese dioxide, chromium oxide and iron oxide are used as raw materials, mixed by a solid phase mixing method, and then calcined at 800°C for 10 hours to obtain layered-spinel two-phase composite doped lithium manganate.
[0045] Example 5
[0046] A high-capacity layered-spinel two-phase composite doped lithium manganate with a structural formula of Li 0.85 Mn 0.8 Cr 0.1 Al 0.1 O2. Lithium carbonate, manganese dioxide, chromium oxide and aluminum oxide are used as raw materials, mixed by a solid phase mixing method, and then calcined at 750°C for 12 hours to obtain layered-spinel two-phase composite doped lithium manganate.
[0047] Example 6
[0048] A high-capacity layered-spinel two-phase composite doped lithium manganate with a structural formula of Li 0.65 Mn 0.9 Cr 0.1 O2. Lithium carbonate, manganese dioxide and chromium oxide are used as raw materials, mixed by solid phase mixing method, and then calcined at 700°C for 8h to obtain layered-spinel two-phase composite doped lithium manganate.
[0049] Example 7
[0050] A high-capacity layered-spinel two-phase composite doped lithium manganate with a structural formula of Li 0.95 Mn 0.9 Cr 0.05 Y 0.05 O2. Lithium carbonate, manganese dioxide, chromium oxide and yttrium oxide are used as raw materials, mixed by a solid phase mixing method, and then calcined at 850°C for 6 hours to obtain layered-spinel two-phase composite doped lithium manganate.
[0051] Example 8
[0052] A high-capacity layered-spinel two-phase composite doped lithium manganate with a structural formula of Li 0.9 Mn 0.9 Al 0.1O2. Lithium carbonate, manganese dioxide and aluminum oxide are used as raw materials, mixed by a solid phase mixing method, and then calcined at 900°C for 10 hours to obtain layered-spinel two-phase composite doped lithium manganate.
[0053] Table 2 Performance test results of Examples 1-8
[0054]
[0055] It can be seen from Table 2 that the electrochemical properties of layered-spinel two-phase composite doped lithium manganese oxide are closely related to the elemental composition and sintering conditions of the material, but in general, the materials in each embodiment have relatively excellent comprehensive electrochemical properties. However, in order to further improve the performance, the preparation conditions of the material can be further optimized.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-capacity layered-spinel two-phase composite doped lithium manganese oxide, characterized in that: The structural formula is Li x Mn 1- y MyO2, wherein x=0.85-0.95, y=0.1-0.2, M is one or more of Al, Cr, Fe, Y; and includes C2 / m layered structure and Fd-3m spinel structure.
2. The high-capacity layered-spinel two-phase composite doped lithium manganate according to claim 1, characterized in that: The molar ratio of the C2 / m layered structure to the Fd-3m spinel structure is (1%:99%)-(99%-1%).
3. The high-capacity layered-spinel two-phase composite doped lithium manganate according to claim 2, characterized in that: The molar ratio of the C2 / m layered structure to the Fd-3m spinel structure is (50%:50%)-(99%-1%).
4. The high-capacity layered-spinel two-phase composite doped lithium manganate according to claim 1, characterized in that: The high-capacity layered-spinel two-phase composite doped lithium manganate has a 0.1C first charge capacity of 220-270 mAh / g and a first efficiency of 50%-80%.
5. A method for preparing the high-capacity layered-spinel two-phase composite doped lithium manganate according to any one of claims 1 to 4, characterized in that: include: The Li compound, the Mn compound and the metal M compound are weighed in a stoichiometric ratio, mixed evenly by a solid phase method or a liquid phase method, and the mixed dry materials are calcined at a high temperature to obtain the high-capacity layered-spinel two-phase composite doped lithium manganate.
6. The method for preparing high-capacity layered-spinel two-phase composite doped lithium manganate according to claim 5, characterized in that: The Li compound includes one or more of lithium carbonate, lithium oxide, lithium hydroxide and lithium nitrate; the Mn compound is one or more of manganese oxide, hydroxide, carbonate, nitrate, chloride and sulfate; the metal M compound is one or more of the oxide, hydroxide, carbonate, nitrate, chloride and sulfate corresponding to the metal M.
7. The method for preparing high-capacity layered-spinel two-phase composite doped lithium manganate according to claim 5, characterized in that: The high temperature calcination temperature is 500-1000° C., and the calcination time is 2-25 hours.
8. The method for preparing high-capacity layered-spinel two-phase composite doped lithium manganate according to claim 5, characterized in that: The high-temperature calcination is carried out in a mixed atmosphere of inert gas and oxygen, and the molar ratio of the inert gas to oxygen is 1:(0-100).
9. The method for preparing high-capacity layered-spinel two-phase composite doped lithium manganate according to claim 8, characterized in that: The high-temperature calcination is carried out in a mixed atmosphere of inert gas and oxygen, and the molar ratio of the inert gas to oxygen is 1:(0-1).
10. The method for preparing high-capacity layered-spinel two-phase composite doped lithium manganate according to claim 5, characterized in that: The solid phase method comprises fully mixing the Li compound, the Mn compound and the metal M compound by ball milling or high-speed mixer, wherein the ball mill has a rotation speed of 200-800 r / min, a ball milling time of 1-72 h, and a ball-to-material weight ratio of (5-50):1; the high-speed mixer has a rotation speed of 500-10000 r / min, and a mixing time of 1-72 h.
11. The method for preparing high-capacity layered-spinel two-phase composite doped lithium manganate according to claim 5, characterized in that: The liquid phase method dissolves the soluble salts corresponding to Mn and M in water to obtain a liquid phase mixture; then, an excess of soluble alkali or soluble carbonate is added dropwise to the liquid phase mixture under stirring to form a precipitate of Mn and M; the precipitate is filtered, washed, and dried to obtain a dry material; and the dry material is uniformly mixed with a Li compound by a solid phase method.
Citation Information
Patent Citations
High-performance lithium manganate anode material and preparation method thereof
CN102751482A
Low-cobalt doped spinel-layered structure lithium nickel manganate two-phase composite cathode material preparation method
CN109088067A
High-voltage lithium ion battery cathode material and preparation method thereof
CN102569781A
High-manganese-based material with composite structure and preparation method and application of high-manganese-based material
CN113889617A
